The role of open innovation in fostering SMEs' business model innovation during the COVID-19 pandemic - Jabeen, Fauzia; Belas, Jaroslav; Santoro, Gabriele; Alam, Gazi Mahabubul (Emerald, 2022)
The economic crisis triggered by the COVID-19 pandemic has had significant consequences on the activities of companies worldwide. This study aims to unveil how open innovation fostered business model innovation in small and medium enterprises (SMEs) during the pandemic.